Emma's Willow: Historical Anxiety, Mormon Pilgrimage and Nauvoo's Mater Dolorosa. (27th October 2016) - Blythe, Christopher James
ABSTRACT: Religious institutions establish collective identities through the production of a usable past, and thereby provide adherents with a sense of heritage. This article examines how this process functions in a Mormon pilgrimage site, Nauvoo, Illinois, where not one but two competing institutions, the Church of Jesus Christ of Latter-day Saints (LDS) and Community of Christ, have established alternative narratives of identity. I focus on the thousands of (almost exclusively) LDS pilgrims who visit the town each summer. I argue that the presence of multiple interpretations raises significant anxieties for many of these pilgrims. In an attempt to mediate these anxieties a vernacular religious site, a willow tree, is employed to point pilgrims to a Saint figure, Emma Smith, Joseph Smith Jr.'s widow, in order to fortify an alternative narrative existing outside of either official representation of Nauvoo's past.